Grooming Training Berbasis Training Need Analysis untuk Mendukung Profesionalisme dan Kualitas Pelayanan Karyawan Hotel Gets Premiere Semarang - Khoirunisa Azahra; Laila Listiana Ulya; Galih Lintang Pratiwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Human resources, particularly employee competence, appearance, and professional image, are important factors in creating service quality within the hospitality industry. Based on the results of a Training Need Analysis (TNA) conducted through observations and interviews, inconsistencies were found in the implementation of employee grooming standards at Gets Premiere Hotel Semarang. Therefore, a Hospitality Appearance Excellence Training program consisting of grooming refreshment training and beauty class sessions was conducted to improve employees’ understanding, awareness, and consistency in applying hotel grooming standards. The training evaluation was carried out using the Kirkpatrick Model focusing on the reaction, learning, and behaviour aspects through an online feedback questionnaire, post-training quiz, and grooming compliance check inspection. The results showed that participants responded positively to the training and demonstrated a good understanding of hotel grooming standards. In addition, the inspection results indicated an improvement in grooming compliance across all observed aspects, including personal hygiene, which increased from 65% to 82%, appearance from 70% to 95%, and the use of uniforms and work attributes from 64% to 90%. Training designed based on organizational needs was considered relevant in supporting the implementation of employee grooming standards within the hotel work environment, although periodic monitoring and reinforcement are still needed to maintain consistent workplace behaviour.